Information-bibliographical service of scientific and technical problem of „Application of protective coatings as well as protective and decorative metal coatings" - Regina Varnienė (Knygotyra)
The article is devoted to the analysis of information models dealing with the problem of the application of protective coatings as well as protective and decorative metal coatings.